Ras superfamily GTPases and signal transduction in Euglena gracilis - Field, Mark C (Protist, 2024)
Biological complexity is challenging to define, but can be considered through one or more features, including overall genome size, number of genes, morphological features, multicellularity, number of life cycle stages and the ability to adapt to different environments. Euglena gracilis meets several of these criteria, with a large genome of ∼38,000 protein coding genes and a considerable ability to survive under many different conditions, some of which can be described as challenging or harsh. Potential molecular exemplars of complexity tying these aspects together are signalling pathways, including GTPases, kinases and ubiquitylation, which increase the functionality of the gene-encoded proteome manyfold. Each of these examples can modulate both protein activity and gene expression. To address the connection between genome size and complexity I have undertaken a brief, and somewhat qualitative, survey of the small ras-like GTPase superfamily of E. gracilis. Unexpectedly, apart from Rab-GTPases which control intracellular transport and organelle identify, the size of the GTPase cohort is modest, and, for example, has not scaled with gene number when compared to the close relatives, trypanosomatids. I suggest that understanding the functions of this protein family will be vital to uncovering the complexity of E. gracilis biology.
Keywords: genom; Euglena gracilis; ras Proteins; Diversity; signální transdukce; Signal Transduction; Signal transduction; Proteome; proteom; Ras; Humans; Euglena; Biological complexity; Small GTPases; Ras proteiny; lidé; Genome